181k views
5 votes
4-3x032-2-2x255555666666666666

1 Answer

5 votes

SOLUTION

Given the question in the image, the following are the solution steps to answer the question.

STEP 1: Write the given expression


4^(-3)*4^0

STEP 2: Simplify the expression


\begin{gathered} 4^(-3)*4^0 \\ \mathrm{Apply\: exponent\: rule}\colon\quad \: a^b*\: a^c=a^(b+c) \\ 4^(-3)*\: 4^0=4^(-3+0) \\ \mathrm{Add/Subtract\: the\: }indice\mathrm{s\colon}\: -3+0=-3 \\ =4^{\mleft\{-3\mright\}} \\ \mathrm{Apply\: exponent\: rule}\colon\quad \: a^(-b)=(1)/(a^b) \\ 4^{\{-3\}}=(1)/(4^3) \end{gathered}

Hence, the expression is equivalent to:


(1)/(4^3)

User SnazzyBootMan
by
6.7k points